Optimalisasi Peran Masyarakat dalam Mencegah Kasus Pencemaran Lingkungan Hidup di DAS Meninting Desa Midang - Taufik, Zahratul'ain; Raodah, Putri; Handalusia, Vici (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The Meninting River Basin in Midang Village, located in West Lombok Regency, is one of the rivers that has been contaminated by microplastic waste. Therefore, it is deemed necessary to optimize public knowledge regarding the management of waste generated from daily life. This community engagement process goes through four steps. First, by conducting observations of the environmental issues at hand; the second step involves analyzing the problem-solving approach and it is found that there is a need to optimize the role of the community in preserving the environment. The third step is the preparation for the execution of the community engagement, encompassing planning and organizing the implementation of activities. The fourth step is the execution of the community engagement carried out through lectures and discussions, simultaneously disseminating regulations regarding environmental protection and management. This activity subsequently generates new knowledge for the community to be able to manage household waste wisely and economically. The goal of this activity is for residents to spread the acquired information or knowledge to others, in order to create business opportunities for the community and to maintain a cleaner environment.